Wave climate conditions of the MUSAN underwater park in Ayia Napa with emphasis in extreme events - Kozyrakis, Georgios V.; Nikolaidis, Andreas; Zodiatis, George; Galanis, George; Alexandrakis, George; Metheniti, Vassiliki; Parasyris, Antonios; Kampanis, Nikolaos A. (Technical Annals, 2024)
The wave parameters in the MUSAN underwater park in Ayia Napa, Cyprus http://www.musan.com.cy/en/home were examined for a period of 5 months, December 2021 to April 2022, by means of numerical analysis tools based on the application of a nested Delft3D-WAVE (SWAN wave model) targeting the near coastal sea area. The implemented wave model used an ultra-high-resolution bathymetry of 5m, which was constructed based on local Lidar observations and EMODnet bathymetry data. The SKIRON forecasting high frequency winds and the CYCOFOS forecasting waves were used, respectively for surface forcing and lateral boundaries. The analysis of the obtained wave parameters, as well as of the wave induced forces-pressure over 4 sites closely surrounding the MUSAN underwater park in Ayia Napa demonstrate that seven extreme wave events occurred during the examined period, one in December 2021, four in January 2022 and two in March 2022. Each extreme wave event lasted for a time of few hours, with maximum SWH between 2.50 to 3.30m and maximum wave induced pressure at the sea surface between 220 to 354kPa. At the subsurface water layers during the extreme wave events, the wave induced pressure in general is decreased, where at the water depth of 2m the maximum wave induced pressure varied between 200 to 299kPA, while at the water depth of 4m the maximum wave induced pressure varied between 180 to 270kPa. The local authorities responsible for the MUSAN underwater park, after the accomplishment of the present study confirmed that the damages of the underwater structures of the park were caused during the wave extreme events in December 2021.